Laboratory assays in infantile atopic dermatitis. - Cavagni, G.; Caffarelli, C.; Terzi, V.; Chiossi, C.; Perrone, F.; Borghi, A. (European Journal of Pediatric Dermatology, 2018)
After some preliminary remarks regarding the immune pathogenesis of the atopic reaction, the Authors review the "in vivo", challenge and "in vitro" tests, that are useful for the diagnosis of atopic dermatitis. They also mention other examinations such as the study of the intestinal permeability to sugars and proteic macromolecules. The latter examinations should now be limited to the research. The Authors conclude that laboratory examinations should be carefully evaluated and related to the clinical features of atopic dermatitis.